Content of Total Polyphenols in Biodynamic Organic Acid Lime (Citrus latifolia Tanaka) Clarified by Microfiltration - Viana, Daniela Soares; Carvalho, Lucia Maria Jaeger de; Ribeiro, Ediane Maria Gomes; Ortiz, Gisela Maria Dellamora (IntechOpen, 2012)
None